1987
DOI: 10.1177/00220345870660052301
|View full text |Cite
|
Sign up to set email alerts
|

Selection for Streptococcus mutans with an Altered Xylitol Transport Capacity in Chronic Xylitol Consumers

Abstract: The effect of long-term consumption of refined xylitol on the natural populations of S. mutans in the human oral cavity has been investigated. Fifty-four S. mutans strains were isolated from adults and children who had been consuming commercial food products containing xylitol for a period of from 1 1/2 to 10 years. Twenty isolates were also obtained from control subjects who had never consumed xylitol-containing commercial food products. The inhibitory effect of xylitol on the isolated strains was determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0
20

Year Published

1995
1995
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(81 citation statements)
references
References 26 publications
3
58
0
20
Order By: Relevance
“…Notably, the now-extensive literature on xylitol inhibition of caries (Mäkinen et al, 1995;Isokangas et al, 2000), usually monitored by measure of frank cavitation of lesions into the dentin, is associated with what might seem to be paradoxical emergence among frequent users of xylitol of X r S. mutans in the mouth (Trahan and Mouton, 1987). The present observations suggest that, in fact, X r strains of S. mutans are of diminished virulence by virtue of compromised colonization of the teeth and compromised ability to induce lesions that penetrate dentin, i.e., to the point that they would have been scored in those clinical studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the now-extensive literature on xylitol inhibition of caries (Mäkinen et al, 1995;Isokangas et al, 2000), usually monitored by measure of frank cavitation of lesions into the dentin, is associated with what might seem to be paradoxical emergence among frequent users of xylitol of X r S. mutans in the mouth (Trahan and Mouton, 1987). The present observations suggest that, in fact, X r strains of S. mutans are of diminished virulence by virtue of compromised colonization of the teeth and compromised ability to induce lesions that penetrate dentin, i.e., to the point that they would have been scored in those clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Xylitol inhibition of caries has attracted considerable interest (Scheinin and Mäkinen, 1975;Mäkinen et al, 1995;Isokangas et al, 2000;Söderling et al, 2000), as has the puzzling emergence, in the mouths of habitual xylitol users, of S. mutans that are resistant to metabolic inhibition by xylitol (X r ) (Trahan and Mouton, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Based on available bacteriologic information [Trahan and Mouton, 1987;Trahan et al, 1992;Trahan, 1995] and field experience from clinical caries trials involving xylitol, it appears that xylitol does exert specific biochemical effects on certain strains of mutans streptococci. Such effects include the mere reduced growth rate of those bacteria in the presence of xylitol, as well as more specific chemical effects, such as weakened adhesivity of the bacteria onto surfaces, increased rate of proteolytic activity of the bacteria, dampening of the acidogenic potential of sucrose, incorporation of xylitol into the bacterial cells with concomitant intracellular accumulation of a toxic xylitol phosphate [Trahan, 1995] and related effects [Mäkinen, 1993].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the anticariogenic effect of xylitol lasts for several years after the practice of consuming xylitol daily has been discontinued and is associated partly with the reduction in the total levels of S. mutans and partly with the decrease in the amount and adhesiveness of dental plaque (8). Some studies have failed to document any long-term decrease in the amount of S. mutans bacteria, however (13,19), and this has been explained by the selection of bacterial strains: habitual use of xylitol may select S. mutans strains which are up to 87% nonexpressive of the fructose phosphotransferase enzyme (17) and are thought to have lower adhesiveness to enamel and, therefore, lower virulence (7,12).…”
Section: Fig 2 In Vitro Growth Of S Mitismentioning
confidence: 99%